Elucidating the role of CYFIP2 in conferring cisplatin resistance in esophageal squamous cell carcinoma - Peipei Zhang; Weiguang Zhang; Zhinuan Hong; Junfei Jiang; Ningzi Wu; Jihong Lin; Mingqiang Kang (Scientific Reports)
Abstract Cisplatin (CDDP) serves as a vital component in the chemotherapeutic approach to treat esophageal squamous cell carcinoma (ESCC). However, prolonged CDDP application frequently culminates in resistance, compromising therapeutic outcomes. Through genome-wide CRISPR library screening, our study elucidates the mechanisms underlying this resistance, pinpointing CYFIP2 as a pivotal mediator. Notably, the involvement CYFIP2 is characterized by pronounced autophagic activity and the modulation of multiple cellular pathways. Empirical validation was achieved by treating ESCC cell lines with CDDP, which resulted in an upsurge of CYFIP2 expression. The functional impact of CYFIP2 was further delineated through knockdown experiments, where a marked suppression in cell proliferation was observed, alongside a discernible decline in reactive oxygen species levels. This was complemented by a suite of assays and microscopic techniques, including GFP-LC3, mRFP-GFP-LC3, electron microscopy and western blot, which collectively affirmed the inhibitory effect of CYFIP2 knockdown on autophagic processes, particularly impeding autophagosome formation and their subsequent fusion with lysosomes. In vivo studies have also confirmed that CYFIP2 knockdown limits tumor progression and increases CDDP efficacy. Conclusively, our findings introduce CYFIP2 as a novel contributor to CDDP resistance in ESCC, underscoring its potential as a therapeutic target. This revelation not only deepens our understanding of resistance mechanisms but also paves the way for novel oncotherapeutic strategies, promising enhanced treatment efficacy against ESCC.